The Effectiveness of Mobile Assisted Language Learning (MALL) in Improving Vocabulary Mastery - Linda Tiwi Diarni; Ahmad Faruk (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
The study entitled "The Effectiveness of Mobile-Assisted Language Learning (MALL) in Improving Vocabulary Mastery" aims to determine the extent to which the use of mobile technology can contribute significantly to improving students' English vocabulary mastery. A qualitative approach with a descriptive design was used in this study. Data were collected through in-depth interviews, observations, and document analysis involving students and English teachers who used mobile-based learning applications such as Duolingo and Quizlet. Data analysis was conducted interactively, including data reduction, presentation, and conclusion drawing, with triangulation techniques used to ensure validity. The findings show that MALL significantly improves students' vocabulary mastery, including comprehension, pronunciation, and the ability to use vocabulary in context. In addition, MALL has been shown to increase student motivation to learn through features such as gamification, instant feedback, and flexibility in learning time and location. Teachers also experienced positive impacts, particularly in creating a more effective, diverse, and student-centered learning environment, as well as in shifting their role towards that of a learning facilitator. In conclusion, this study shows that MALL is an effective, innovative, and relevant strategy for improving English vocabulary learning and meeting the needs of learners in the digital age.